New Trends in Behavioral Economics: A Content Analysis of Social Communications of Youth - Nur-Al-Ahad, Md; Nusrat, S. (Business Ethics and Leadership, 2019)
This paper summarizes the arguments and counterarguments within the scientific discussion on the issue of psychological factors that determine the level of rational behavior of an individual in decision-making, the nature of his/her interpersonal and intergroup interaction. The aim of the study is to analyze the main types of youth behavior, depending on the structure of the society around them and the subject of discussion. The urgency of solving this scientific problem is the constant transformation of the norms and rules of behavior declared in society, influenced by the development of information technologies, opening access to scientific and humanitarian knowledge, increasing the number of deviant behavior of young people, difficulties in their adaptation in society, etc. The study of the main psychotypes of the individual in the article is carried out in the following logical sequence: the starting point of the study is the assumption of a change in youth behavior depending on the object of discussion and the environment in which it is located, after which the authors use the content analysis method to study the behavior of students presented in different WhatsApp groups. The object of the study was the students of some Malaysian universities. The systematization of literary sources and further analysis testify to the continued use of smartphones, which support many applications, in a daily life. WhatsApp has been identified as one of the most popular applications used by smartphone users for both communication and education. The study empirically confirms the successful use of WhatsApp by university students and teachers as a means of communication and knowledge transfer. In the study, the authors have identified the topic of discussions, type of messages and contributors as well as silent readers involved in WhatsApp groups. All the messages exchanged are categorized based on four main topics which are study, personal, current issues and others. It has been found all groups have been able to achieve their respective group objectives. Overall, the most frequently discussed topic for each group is regarding study and personal interest. Keywords: behavioral economics, WhatsApp, students’ behavior, content analysis.